Externalities from Private Pensions in the Spanish Income Tax - Guerre, Asunción Arner (International Journal of Economics and Financial Issues, 2026)
Fiscal incentives of pension plans in the Spanish Income tax consist of tax credits on contributions of the taxpayer, although the incomes obtained are taxed at the individual’s marginal rate. Nowadays, occupational and personal private pensions (the second and third pillar of social insurance) are differentiated. Since 2009, the latest reform of the Financing System of the Autonomous Communities of common regime and Cities with Statute of Autonomy (AFS), the Income tax collection has been transferred to regional governments, up to 50%, with the state and regional tax base remaining the same, while the regional tax rates differ across Autonomous Communities. Subsequently, savings from tax credits on contributions to pension plans and taxation of pension payments differ across communities. This work aims to study the relationship between the regional Income tax (RIT) yield and the tax credit variable in RIT from contributions to private pensions (TBD). Estimates are obtained from Dynamic Panel Data for the fifteen Autonomous Communities of the common regime for 2003-2022, using the Instrumental Variables (IV) estimator and its generalization, the Generalized Method of Moments (GMM). The main result is that the elasticity of RIT to TBD is negative at 0,19; also, fiscal incentives generated vertical and horizontal externalities in reference to Income tax.